The Impact of Competition on Bank Orientation and Specialization (new titel: The impact of competition on bank orientation) - Hans Degryse; Steven Ongena (Center for Economic Studies and ifo Institute (CESifo), 2004)
How do banks react to increased interbank competition? Recent banking theory offers conflicting predictions about the impact of competition on bank orientation - i.e., the choice of relationship based versus transactional banking - and bank industry specialization. We empirically investigate the impact of interbank competition on bank branch orientation and specialization. We employ a unique data set containing detailed information on bank-firm relationships and industry classification. We find that bank branches facing stiff local competition engage relatively more in relationship-based lending but specialize somewhat less in a particular industry. Our results illustrate that competition and relationships are not necessarily inimical.
Keywords: 330; bank orientation; bank industry specialization; competition; lending relationships